Long-term cellular immune response in immunocompromised unvaccinated COVID-19 patients undergoing monoclonal antibody treatment - Thümmler, Laura; Konik, Margarethe; Lindemann, Monika; Fisenkci, Neslinur; Koldehoff, Michael; Gäckler, Anja; Horn, Peter A.; Theodoropoulos, Fotis; Taube, Christian; Zettler, Markus; Anastasiou, Olympia Evdoxia; Braß, Peer; et al. (Frontiers in Immunology, 2022)
Immunocompromised patients are at increased risk for a severe course of COVID-19. Treatment of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection with anti-SARS-CoV-2 monoclonal antibodies (mAbs) has become widely accepted. However, the effects of mAb treatment on the long-term primary cellular response to SARS-CoV-2 are unknown. In the following study, we investigated the long-term cellular immune responses to SARS-CoV-2 Spike S1, Membrane (M) and Nucleocapsid (N) antigens using the ELISpot assay in unvaccinated, mAb-treated immunocompromised high-risk patients. Anti-SARS-CoV-2 mAb untreated though vaccinated COVID-19 immunocompromised patients, vaccinated SARS-CoV-2 immunocompromised patients without COVID-19 and vaccinated healthy control subjects served as control groups. The cellular immune response was determined at a median of 5 months after SARS-CoV-2 infection. Our data suggest that immunocompromised patients develop an endogenous long-term cellular immune response after COVID-19, although at low levels. A better understanding of the cellular immune response will help guide clinical decision making for these vulnerable patient cohorts.